(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This thesis explores the shifting process of sustainable management practices in Central Higher Education Institutions (HEIs) and changes in the general organizational systems and environments as well as the overall effects on organizational performance and stakeholders’ state. Following the case study approach that targets are often linked to sustainability and using the experience of previous studies, the research assesses how sustainability concepts have been implemented into HEIs’ business and strategic models and how lean management and intellectual capital complement each other for sustainable development.